Differential Relationships Between the Montreal Cognitive Assessment and Informant-Rated Cognitive Decline Among Mexican Americans and Non-Hispanic Whites. (July 2022) - Briceño, Emily M.; Mehdipanah, Roshanak; Gonzales, Xavier F.; Heeringa, Steven G.; Levine, Deborah A.; Langa, Kenneth M.; Zahs, Daniel; Garcia, Nelda; Longoria, Ruth; Vargas, Alejandro; Morgenstern, Lewis B.
Objectives: We compared the concurrent validity of the Montreal Cognitive Assessment (MoCA) with other cognitive screening instruments among Mexican Americans (MA) and non-Hispanic whites (NHW). Methods: In a community-based study in Nueces county, Texas (5/2/18-2/26/20), participants 65+ with MoCA ≤25 completed the Harmonized Cognitive Assessment Protocol. Regressions examined associations between MoCA and: 1) Mini Mental State Examination (MMSE); 2) abbreviated Community Screening Interview for Dementia (CSI-D); 3) Informant Questionnaire on Cognitive Decline in the Elderly (IQCODE). Results: MA (n = 229) and NHW (n = 81) differed by education but not age or sex. MoCA and cognitive performance associations (MMSE, CSI-D-Respondent) did not differ between MA and NHW (p's > .16). MoCA and informant rating associations (IQCODE, CSI-D-Informant) were stronger in NHW than MA (NHW R 2 = 0.39 and 0.38, respectively; MA R 2 = 0.30 and 0.28, respectively). Discussion: Our findings suggest non-equivalence across cognitive screening instruments among MAs and NHWs.